An analysis of social aspects in CSCL: a SML on design and evaluation of sociability to (re)qualify these environments - Garrido, Filipe A.; do Rêgo, Beatriz B.; Rosa, Jean C. S.; Matos, Ecivaldo de S. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2024)
In computer-supported cooperative work, especially in Computer Supported Collaborative Learning (CSCL), there is a high dependence on interpersonal relationships in the learning process. Therefore, sociability is an essential aspect for the success of this approach. CSCL systems have as their fundamental principle the intermediation of relationships between people to share resources, facilitate teamwork and facilitate the flow of information in the teaching-learning process. CSCL environments tend to bring together many students with a wide range of social and cultural characteristics. They interact with their peers to learn and build knowledge collaboratively. This article aims to present the results of a systematic mapping of the literature that presents challenges and solutions related to sociability in the design and evaluation of CSCL systems. The systematic mapping of literature was carried out through searches in four scientific databases, adopting quality criteria to refine the findings into categories. We identify techniques, methods and formalisms and categorize them according to conception or evaluation, focusing on sociability in CSCL. We hope that the explicit tools and approaches described in this study can enable projects and evaluations of these environments that prioritize essential social aspects in interaction, verifying the quality of sociability in these environments.